ПРАВОВІ ЗАСАДИ ЗАБЕЗПЕЧЕННЯ КРИМІНОЛОГІЧНОЇ БЕЗПЕКИ - Мозоль, Станіслав Анатолійович (SUPREMANCE OF LAW, 2018)
The article is devoted to analysis of legal basics of criminological security and development of the Institute for criminological and socio-legal expertise in Ukraine. The author defi nes the basic principles for carrying out scientific expertise of draft laws to be followed in the process of organizing this activity.